LANGUAGE VARIATION IN THE LINGUISTIC LANDSCAPE OF THE CHINATOWN AREA IN MAGELANG CITY - syafira, Vira; Mulyani, Mimi; Pradita, Linda Eka (Universitas Muhammadiyah Makassar, 2026)
Linguistic landscape research examines written language in public spaces as a reflection of societal linguistic practices across various forms of public signage. Theoretically, the linguistic landscape has two main functions: informative and symbolic. However, in practice, language use in the observed Chinatown area of Magelang tends to emphasize the informative function. This gap between theoretical concepts and actual practice motivated the present study, which was conducted in the Chinatown area of Magelang City. This study aims to identify and describe forms of language variation and the functions of the linguistic landscape in the area. This research employs a qualitative, descriptive research design. The data sources consist of visual texts found in public spaces, including signboards, banners, advertisements, and road signs. Data were collected through observation and documentation techniques. Data analysis was conducted using the equivalence method with the determinant element sorting technique Pilah Unsur Penentu (PUP), comprising the following stages: data collection, classification by language variation type, analysis of linguistic elements, and conclusion drawing. The results show the presence of monolingual, bilingual, and multilingual language variations, with monolingual language use being the most dominant. The language functions identified include informative and symbolic functions, with the informative functions being the most dominant. These findings indicate that the linguistic landscape in the Chinatown area of Magelang City is more oriented towards conveying information in public spaces.